(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2014)
This study aimed to determine the correlation between physicochemical parameters namely salinity, pH and temperature with the occurrence of V. parahaemolyticus in estuarine river of Sg. Sarawak. A total of 72 water samples (surface and deep waters) were collected from the study site. A combination of MPN and PCR to detect and quantify the presence of V. parahaemolyticus, targeting the regulatory gene, toxR was performed. Over the 12-weeks sampling period, site 2 and site 3 recorded 100% presence of V. parahaemolyticus while site I was only 17%. The conditions found in site 2 (9.75‰, pH 7.2, 29.65 °C) and 3 (10.3‰, pH 7.36, 30 °C) favored the presence of V. parahaemolyticus (669 cells 10 ml-1 and 922 cells 10 ml-1 respectively) than site 1 (0.68‰, pH 6.75, 29.2 °C). Statistical analysis showed that the abundance of total V. parahaemolyticus counts was correlated well with the water salinity (Pearson correlation coefficient, r = 0.699; P < 0.01) and water temperature (r = 0.531; P < 0.01) but less correlated with water pH (r = 0.343; P < 0.01).